The Effect of Gratitude on the Happiness Levels of Students in the Faculty of Da’wah and Communication: A Study at Universitas Islam Negeri Sumatera Utara - Autari Putri Amanda; Nashrillah Nashrillah (Institut Agama Islam Negeri Kerinci, Indonesia, 2026)
Happiness serves as a fundamental pillar of university students’ psychological well-being; yet, empirical investigations targeting cohorts within Islamic communication disciplines remain underrepresented in the literature. Addressing this knowledge gap, the present study quantified the impact of gratitude on happiness levels among undergraduate students enrolled in the Faculty of Da’wah and Communication at Universitas Islam Negeri Sumatera Utara. Utilizing a quantitative predictive correlational design, data were gathered through Likert-scale questionnaires administered to a purposively sampled cohort of 100 active students spanning their 2nd, 4th, and 6th academic semesters. Simple linear regression executed via IBM SPSS Statistics (Version 25.0) revealed a statistically significant positive effect of gratitude on student happiness (p < .05, p = .000). The regression equation, Y = 18.419 + 0.492X, indicates that each unit increase in gratitude corresponds to a 0.492-unit enhancement in happiness. Furthermore, an Adjusted R² value of .314 demonstrates that gratitude accounts for 31.4% of the variance in happiness levels, leaving the remaining 68.6% attributable to unexamined external variables. These empirical insights underscore gratitude as a viable psychological determinant of student happiness, offering actionable implications for higher education institutions to design targeted character-building initiatives and well-being interventions